Spring report, Bery Engebretsen, May 31, 1998 - Engebretsen, Beryet al (1998)
An annotated list of birds sighted by Bery Engebretsen dated May 31, 1998. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of spring 1998. Epson - sheet feed/flatbed